Vibration parameters identification of turbomachinery rotor blades under transient condition using Blade Tip-Timing measurements. (October 2021) - Bornassi, S.; Berruti, T.M.; Firrone, C.M.; Battiato, G.
Abstract: During run ups and run downs, the rotating blades are subjected to fluctuating forces with time dependent frequencies and the dynamic response of the blades around the resonance crossings deviates from the stationary response. This paper presents a procedure to identify the vibration parameters of rotating blades under this non-stationary condition. An analytically based solution of a single degree of freedom (SDOF) system exposed to a transient harmonic excitation with linear time varying frequency is used for parameters identification. This analytical model is fitted into the Blade Tip-Timing (BTT) data and the vibration parameters are determined by a least square optimization technique. A numerical simulator based on a lumped parameter model of the bladed disk assembly is employed to demonstrate the method performance. Afterwards, the accuracy of the method is proved by testing it on the experimental data acquired by BTT and strain gauges on a rotating bladed disk. Highlights: Identification of turbomachinery blade vibration parameters. Presenting a transient model based on a Single Degree of Freedom vibrating system. Numerical and experimental validation of the proposed model. Proof of the transient model performance with respect to the stationary method.